How do you solve 3(-9m + 9) = 5(-m + 45)?

1 Answer
Jul 14, 2015

m=-9

Explanation:

We are given 3(-9m+9)=5(-m+45)

First let's multiply the 3 and the 5 into the parenthesis:

3(-9m+9)=5(-m+45)

3*(-9m)+3*9=5*(-m)+5*45

-27m+27=-5m+225

Let's now add 5m to both sides:

-27m+27=-5m+225

-22m+27=225

and then, subtract 27 from both sides:

-22m+27=225

-22m=198

Now, let's divide both sides by -22:

-22m=198

m=-9

Let's check our answer by plugging in -9 into m:

3(-9m+9)=5(-m+45)

3(-9*(-9)+9)=5(-(-9)+45)

3(81+9)=5(54)

3(90)=270

270=270